Pengaruh Harga dan Suasana Tempat serta Variasi Menu terhadap Kepuasan Konsumen di Restoran Q5 Steak Kabupaten Banyuwangi - Ardianta, Rido Febrian; Wicaksono, Dani Agung; Ton, Sefri; Prayitno, Salvian Setyo; Wilujeng, Ninik Sri Rahayu (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
In the era of globalization, the culinary sector has experienced significant growth, especially in fast food restaurants that focus on optimizing profits. Data from the Indonesian Central Bureau of Statistics shows a 20.76% increase in restaurant businesses compared to the previous year. The success of a restaurant is influenced by taste, menu variety, price, and atmosphere that can attract consumers. Researchers used three independent variables: price, atmosphere, and menu variety. The number of samples in this study was 90 respondents. The analysis method used was multiple linear regression with the help of SPSS version 26 software and hypothesis testing involving the R2 test, F-test, t-test, and Classical Assumption Test to validate the model. The test results showed an adjusted R2 value of 68.3%, indicating that the independent variables used in the model, namely price and atmosphere, as well as menu variety, simultaneously explained changes in consumer satisfaction at Q5 Steak & Bowl Banyuwangi by 68.3%, while the remaining 31.7% was explained by other variables outside this research model. The variables that have a significant influence in this model are price and menu variety because they have sig value <0.05, while the atmosphere of the place does not have a significant influence on consumer satisfaction. Meanwhile, the price variable has the most dominant influence on consumer satisfaction, this is because the price variable has the largest coefficient value compared to the coefficient value of other independent variables, which is 0.577. This research model is free from symptoms of multicollinearity and heteroscedasticity.